Vitamin D, parathyroid hormone and risk factors for coronary artery disease in an elderly Chinese population. Issue 1 (January 2015) - Chen, Wei R.; Chen, Yun D.; Shi, Yang; Yin, Da W.; Wang, Hao; Sha, Yuan
<x xml:space="preserve">Abstract</x> Aims Low vitamin D status has been shown to be associated with coronary artery disease; most studies have involved in adults, but few have involved elderly people. We planned to research the association between vitamin D, parathyroid hormone (PTH) and coronary artery disease in elderly people. Methods A population-based study was conducted among 1245 Chinese participants, aged 60–102 years, in the spring of 2013. Serum 25-hydroxyvitamin D (25 (OH)D) was measured by chemiluminescence assay. The levels of PTH were measured by the electrochemiluminescence immunoassay (ECLIA) method. Results One thousand two hundred and forty-five participants, including 543 women (43.6%), were evaluated in 2013. The median concentrations of serum 25 (OH)D and PTH for the entire group were 16.8 ng/ml and 41.0 pg/ml, respectively. The prevalence rates of diabetes, hypertension, hyperlipidemia and coronary artery disease were significantly different across the 25 (OH)D quartiles. The prevalence rates of diabetes, hypertension, hyperlipidemia and coronary artery disease were also significantly different across the PTH quartiles. In logistic regression analyses, serum 25 (OH)D levels were associated with risk of coronary artery disease in single and multiple regression models (P < 0.05). Serum PTH levels were also associated with the risk of coronary artery disease in single and multiple regression models (P < 0.05). Subgroup analyses stratified by sex or age yielded similar results. Conclusions Serum vitamin D and PTH levels are independently associated with risk of coronary artery disease in a Chinese elderly population.